Reinforcement strategy for medial open-wedge high tibial osteotomy: a finite element evaluation of the additional opposite screw technique and bone grafts. (January 2022) - Zhao, Xing-wen; Fan, Zheng-rui; Ma, Jian-xiong; Ma, Xin-long; Wang, Ying; Bai, Hao-hao; Lu, Bin; Sun, Lei
Highlights: This study clarified the biomechanical changes of lateral hinge area and medial implant area with different fixation configurations after open wedge high tibial osteotomy procedure. The results suggested that the bone graft had superior performance in reinforcing the stability of fixation and reducing the risks of internal fixation failure and lateral hinge fracture. The results demonstrated the fully threaded screw had better biomechanical property than partially threaded screw, which showed comparable performance to the bone graft group. Abstract: Background and objective: bone grafts (bgs) and the opposite screw insertion technique are reported to enhance initial stability after medial open-wedge high tibial osteotomy (OWHTO); however, it is unclear how the general and local biomechanical stability of the proximal tibia is affected by these reinforcement strategies. In this study, we aimed to assess the biomechanical differences among different fixation configurations for OWHTO under two loading conditions using finite element analysis, and to assess the biomechanical contribution of an opposite screw insertion. Methods: Models of the proximal tibia with three different gap defects were created to simulate different distraction heights in OWHTO. Four groups of models were then assembled with different fixation configurations, including the no BG (NBG) group, BG group, partially threaded screw (PT) group, and fully threaded screw (FT) group. Testing loads were applied to simulate the static forces on the knee joint during double-limb and single-limb standing. For each group, the stresses of the lateral hinge area (LHA) and the medial implant area (MIA), the maximum displacement of the tibia and the relative displacement (RD) of the medial gap were evaluated. Results: Compared to NBG group, bone block grafting effectively reduced the stress of the tibia and implant, as well as the maximum displacement of the tibia and the RD of the medial gap. The opposite screw group showed similar trends in alleviating the stress concentration on the LHA and MIA, and contributing to the maintaining the medial gap reduction, especially in the FT group; however, additional stresses were concentrated on the opposite screw itself, which indicated the potential risk of screw breakage. Conclusions: Compared to NBG group, the BG group bone graft showed superior biomechanical advantages in decreasing the risk of implant failure and lateral hinge fracture, and maintaining the reduction in OWHTO. The additional opposite screw provided an extra support to the proximal tibia, with similar contributions to improve the structural stability after osteotomy, especially in the FT group.